A Young Patient With Pancytopenia and Cirrhosis: Unraveling a Telomere Biology Disorder - Jacob R. Lipovac; Lucy Z. Shi (Annals of Internal Medicine: Clinical Cases)
Telomere biology disorders represent a rare spectrum of disease caused by genetic defects of telomere maintenance with multisystem involvement, most often related to organ failure and aging. Ranging in severity, telomere biology disorders can appear in the absence of known risk factors. We present a young patient who developed rapid onset of bone marrow failure and cirrhosis, ultimately found to be due to an underlying disorder of telomere biology with mutations within the PARN and TERT genes.